Antiplatelet effect, safety, and pharmacokinetics of vicagrel in patients with coronary artery disease undergoing percutaneous coronary intervention. Issue 8 (19th April 2022) - Zhao, Xin; Ma, Sicong; Kang, Yi; Tang, Chengchun; Liu, Bin; Jiang, Hong; Zheng, Mingqi; Tang, Yu; Sun, Hongbin; Liu, Yongqiang; Lai, Xiaojuan; Gong, Yanchun; et al.
Abstract: Aims: Vicagrel, a novel antiplatelet prodrug to overcome the residual high platelet reactivity of clopidogrel induced by inactive metabolism and cytochrome P450 (CYP) 2C19 polymorphisms, provides favourable antiplatelet inhibition in healthy volunteers. However, its antiplatelet effect and safety in patients with coronary artery disease (CAD) are unclear. Methods and results: This was a multicentre, randomized, double-blind, triple-dummy, dose-exploring phase II trial comparing the antiplatelet activity and safety of vicagrel at different doses vs. those of clopidogrel in patients with CAD undergoing percutaneous coronary intervention (PCI). The primary endpoint was inhibition of adenosine diphosphate (ADP)-induced platelet aggregation (%IPA) after loading and maintenance doses (LD/MD) at 28 days. Safety endpoints included adverse events (AEs) and Bleeding Academic Research Consortium-defined any bleeding. Pharmacokinetic (PK) profiles and the influence of CYP2C19 polymorphisms were explored in subgroup analysis. Two hundred and seventy-nine patients diagnosed with stable CAD (51.97%), unstable angina (40.86%), and myocardial infarction (7.17%) were randomized to receive vicagrel 20/5 mg (LD/MD), 24/6 mg, or 30/7.5 mg or clopidogrel 300/75 mg in combination with aspirin. %IPAs on Day 28 were 30.19%, 35.02%, 45.61%, and 32.55% for vicagrel 20/5, 24/6, and 30/7.5 mg and clopidogrel, respectively, and were comparable across all groups ( P = 0.0694). The plasma concentration of the vicagrel active metabolite M15-2 had a similar area under curve and T max to those of clopidogrel. There were no significant differences in AEs (4.35%, 0%, 1.45%, and 5.56% for vicagrel 20/5, 24/6, and 30/7.5 mg and clopidogrel, P = 0.6667) or any bleeding (13.04%, 14.06%, 11.59%, and 11.11% for vicagrel 20/5, 24/6, and 30/7.5 mg and clopidogrel, respectively, P = 0.95) across four groups. %IPAs and PK profiles of vicagrel did not vary significantly among different CYP2C19 metabolizers. Conclusion: Vicagrel had comparable antiplatelet effect and safety to clopidogrel in patients with CAD undergoing PCI.